It happened one summer : a novel - Bailey, Tessa (New York : Avon, an imprint of HarperCollinsPublishers, 2021)
"A rom-com about a Hollywood "It Girl" who's cut off from her wealthy family and exiled to a small Pacific Northwest beach town. . . where she butts heads with a surly, sexy local who thinks she doesn't belong."--
Keywords: Man-woman relationships -- Fiction; Ship captains -- Fiction; Washington (State) -- Fiction; Romance fiction